Effects of fission and mitophagy on mitochondrial functionality under accelerated damage conditions: A mathematical modeling approach - Zamora-Ramírez, Ángel J.; Santillán, Moisés (Frontiers in Applied Mathematics and Statistics, 2023)
Mitochondria form a dynamic reticulum in cells, which is constantly remodeled by fusion and fission events. These processes are referred to as mitochondrial dynamics, along with mitochondrial replication (mitogenesis) and degradation (mitophagy). There is growing evidence that mitochondrial dynamics play a role in mitochondrial function quality control. Fission and selective fusion separate dysfunctional mitochondria, allowing mitophagy to remove them. Numerous recent studies have found that physical activity aids in the maintenance of a healthy mitochondrial population by altering mitochondrial dynamics processes such as mitogenesis, fission, and mitophagy. According to some studies, exercise may help to compensate for the mitochondrial damage caused by obesity. However, the underlying mechanisms and how they influence the various processes of mitochondrial dynamics have not been completely clarified. This question is addressed in the current study through the use of an explanatory mathematical model that takes into account the fundamental regulatory elements of mitochondrial dynamics and is consistent with the notion that it plays an important role in the quality control of mitochondrial function. We found by analyzing the model stationary behavior that fission and mitophagy are strictly required for a healthy mitochondrial population, that increasing the rate of mitochondrial damage has a negative impact on the population of functional mitochondria, and that such damage can be mitigated to some extent by increasing fission and/or mitophagy rates. These findings are finally discussed in the context of the benefits of physical activity for mitochondrial population health in obese individuals.